PERUSAHAAN SOSIAL DAN KUBe DI INDONESIA : PELUANG DAN TANTANGAN - Nuryana, Mu'man (Sosio Informa : Kajian Permasalahan Sosial dan Usaha Kesejahteraan Sosial, 2017)
Social enterprise has been acknowledged in Indonesia due to the advantages in achieving inclusive and sustainable growth while helping the poor to improve their economic and social welfare. The main difference with traditional micro, small and medium enterprises is that collective enterprise has a hybrid characteristic in which they adopt business solutions to address social problems. Social and cultural environment is conducive for social entrepreneurship since the country has considerable attention to the issue of people welfare and now is in the movement towards the wider participation of civil society organisation and the private sector on social issues. Social enterprise that has been developing in this country is one of the forms of social enterprise. In its development, this social enterprise involves many poor households at the community level so that it can be viewed as a community-Ââ€based social enterprise. However, the policy environment is still not fully responsive to the growth and development of social enterprise. Social enterprise is still viewed as a traditional micro, small and medium enterprise. Therefore, it requires additional support for social enterprise by providing incentives for mixed financing, improving the sustainable environment for grants, venture capital and external assistance, and recognizing the longer incubation period for social enterprise. To that end, coordination between social sector that gave rise to the birth of that social enterprise with economic sectorÂ  as further foster parent needs to be further improved. Â  Key words: Social enterprise, collective enterprise group, community-Ââ€based social enterprise (perusahaan sosial, kelompok usaha bersama, perusahaan sosial berbasis-Ââ€ komunitas).